Robust functional expression of insect nicotinic acetylcholine receptors provides new insights into neonicotinoid actions and new opportunities for pest and vector control. Issue 8 (7th December 2020) - Matsuda, Kazuhiko
Abstract: Neonicotinoids are selective modulators of insect nicotinic acetylcholine receptors (nAChRs). These widely deployed insecticides interact with the orthosteric sites of nAChRs, not only to activate nAChRs on their own, but also to block the desensitizing component of nAChR responses. To date recombinant vertebrate or insect/vertebrate hybrid nAChRs have been deployed to understand the mechanism of selectivity and diversity of neonicotinoid actions as well as to show that both α/α and α/non‐α interfaces are involved in the interactions with neonicotinoids. However, many of the fine details of insecticide interactions with sites on nAChRs remain to be resolved. The breakthrough of functional expression of insect nAChRs allows such questions to be addressed, not only for neonicotinoids but for other insecticides targeting insect nAChRs. © 2020 Society of Chemical Industry Abstract : Given co‐factor enabled, functional expression of robust insect nicotinic acetylcholine receptors (nAChRs), it is now possible to study in detail the mode of actions of neonicotinoids and related insecticides.